PENGARUH KEPEMIMPINAN TERHADAP EFEKTIVITAS ORGANISASI - Febrian, Wenny Desty; Adriana, Adriana; Asrida, Wan (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2017)
This study examines the effect of leadership on organizational effectiveness. Quantitaviemethod was used to collect data, by the questionnaires, and distributed to employees at PTAdira Dinamika Multi Finance Tbk, Pekanbaru. The results of this study showed that sigvalue of 0.001, fewer than probability value of 0.05. Moreover,leadership has t value of -3.396 with t table of -1.985. In conclusion, leadership significantly explained organizational effectiveness.